Distinct Structures of Scrapie Prion Protein (PrP(Sc))-seeded Versus Spontaneous Recombinant Prion Protein Fibrils Revealed by Hydrogen/Deuterium Exchange - Smirnovas, Vytautas (American Society for Biochemistry and Molecular Biology, 2009)
The detailed structures of prion disease-associated, partially protease-resistant forms of prion protein (e.g. PrP(Sc)) are largely unknown. PrP(Sc) appears to propagate itself by autocatalyzing the conformational conversion and oligomerization of normal prion protein (PrP(C)). One manifestation of PrP(Sc) templating activity is its ability, in protein misfolding cyclic amplification reactions, to seed the conversion of recombinant prion protein (rPrP) into aggregates that more closely resemble PrP(Sc) than spontaneously nucleated rPrP amyloids in terms of proteolytic fragmentation and infrared spectra. The absence of posttranslational modifications makes these rPrP aggregates more amenable to detailed structural analyses than bona fide PrP(Sc). Here, we compare the structures of PrP(Sc)-seeded and spontaneously nucleated aggregates of hamster rPrP by using H/D exchange coupled with mass spectrometry. In spontaneously formed fibrils, very slow H/D exchange in region ∼163–223 represents a systematically H-bonded cross-β amyloid core structure. PrP(Sc)-seeded aggregates have a subpopulation of molecules in which this core region extends N-terminally as far as to residue ∼145, and there is a significant degree of order within residues ∼117–133. The formation of tightly H-bonded structures by these more N-terminal residues may account partially for the generation of longer protease-resistant regions in the PrP(Sc)-seeded rPrP aggregates; however, part of the added protease resistance is dependent on the presence of SDS during proteolysis, emphasizing the multifactorial influences on proteolytic fragmentation patterns. These results demonstrate that PrP(Sc) has a distinct templating activity that induces ordered, systematically H-bonded structure in regions that are dynamic and poorly defined in spontaneously formed aggregates of rPrP.